Stress-kinase regulation of TASK-1 and TASK-3 - Rinné, Susanne; Schmidt, Constanze (Cellular physiology and biochemistry, 2017)
Background/Aims: TASK channels belong to the two-pore-domain potassium (K2P) channel family. TASK-1 is discussed to contribute to chronic atrial fibrillation (AFib) and has been together with uncoupling protein 1 found as a marker protein of brown adipose tissue (BAT) fat. In addition, TASK-1 was linked in a genome-wide association study to an increased body mass index. A recent study showed that TASK-1 inhibition is causing obesity in mice by a BAT whitening and that these effects are linked to the mineralocorticoid receptor pathway, albeit the mechanism remained elusive. Therefore, we aimed to probe whether K2P channels are regulated by serum- and glucocorticoid-inducible kinases (SGKs) which are known to modify many cellular functions by modulating ion channels. Methods: To this end we used functional co-expression studies and chemiluminescence-assays in Xenopus oocytes, together with fluorescence imaging and quantitative PCR experiments. Results: SGKs and proteinkinase B (PKB) induced a strong, dose- and time-dependent current reduction of TASK-1 and TASK-3. SGK co-expression reduced the surface expression of TASK-1/3, leading to a predominant localization of the channels into late endosomes. The down regulation of TASK-3 channels was abrogated by the dynamin inhibitor dynasore, confirming a role of SGKs in TASK-1/3 channel endocytosis. Conclusion: Stress-mediated changes in SGK expression pattern or activation is likely to alter TASK-1/3 expression at the surface membrane. The observed TASK-1 regulation might contribute to the pathogenesis of chronic AFib and provide a mechanistic link between increased mineralocorticoid levels and TASK-1 reduction, both linked to BAT whitening.
Published online: November 27, 2017
Gesehen am 27.06.2018